2020
DOI: 10.1007/s10957-020-01764-0
|View full text |Cite
|
Sign up to set email alerts
|

An Existence Result for Quasi-equilibrium Problems via Ekeland’s Variational Principle

Abstract: This paper deals with the existence of solutions to equilibrium and quasiequilibrium problems without any convexity assumption. Coverage includes some equivalences to the Ekeland variational principle for bifunctions and basic facts about transfer lower continuity. An application is given to systems of quasi-equilibrium problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…On the other hand, it is well known that the sum of two upper semi-continuous function is upper semi-continuous. However, in [8] the authors showed that the same does not hold for transfer upper continuity. In a similar way, it does not hold for upper pseudo-continuity, a contra-example can be found in [29].…”
Section: Definitions Notations and Preliminary Resultsmentioning
confidence: 99%
“…On the other hand, it is well known that the sum of two upper semi-continuous function is upper semi-continuous. However, in [8] the authors showed that the same does not hold for transfer upper continuity. In a similar way, it does not hold for upper pseudo-continuity, a contra-example can be found in [29].…”
Section: Definitions Notations and Preliminary Resultsmentioning
confidence: 99%
“…Bài toán cân bằng là một dạng tổng quát cho việc thiết lập và nghiên cứu của rất nhiều bài toán xuất hiện trong toán học lý thuyết và toán học ứng dụng như kinh tế, kỹ thuật, vật lý, y học và một số lĩnh vực khác nữa, xem Kassay and Rădulescu (2018), Bigi et al (2019). Các chủ đề về bài toán này luôn nhận được sự quan tâm của các nhà toán học, bao gồm điều kiện tồn tại nghiệm, điều kiện ổn định nghiệm, điều kiện đặt chỉnh và các thuật toán tìm nghiệm, xem Anh et al (2018aAnh et al ( , 2018bAnh et al ( , 2019Anh et al ( , 2020Anh et al ( , 2021Anh et al ( , 2022Anh et al ( , 2023aAnh et al ( , 2023b, Blum and Oettli (1994), Cotrina et al (2020), Eslamizadeh and Naraghirad (2020), Muu and Oettli (1992), Oyewole and Mewomo (2020), Tam (2022Tam ( , 2023 và các tài liệu tham khảo trong đó. Bài toán chấp nhận tách lần đầu tiên được giới thiệu trong Censor and Elfying (1994) trong việc mô hình các bài toán ngược xuất phát từ việc khôi phục pha và phục chế hình ảnh trong y học, xem Byrne (2002).…”
Section: Giới Thiệuunclassified
“…En [13] se estudia la existencia de soluciones para QEPs usando hipótesis más débiles que la semicontinuidad inferior, mediante el uso del concepto de transfer lower continuity.…”
unclassified